2011
DOI: 10.1111/j.1747-7379.2010.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Transnational Home Engagement among Latino and Asian Americans: Resources and Motivation

Abstract: Is immigrant groups' assimilation to host society at odds with their engagement with the country of ancestral origin? This study divides the concept of assimilation into socioeconomic resources and attachment to host society, and argues that assimilation and transnational perspectives are coexisting paradigms. Analyses using the nationally representative samples of Latino and Asian Americans indicate that 1) higher-order generations reduce the odds of home country engagement, i.e. frequent return visits, 2) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 32 publications
0
50
0
3
Order By: Relevance
“…While Tamaki (2011) andWaldinger (2008) have found American citizenship of high relevance for return visits in the North American context, in this paper, I have shown that having dual citizenship is significantly positively linked to return visits compared to having only home country citizenship. In other words, dual citizenship is strongly linked to more mobility, allowing migrants to be simultaneously embedded in multiple contexts.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…While Tamaki (2011) andWaldinger (2008) have found American citizenship of high relevance for return visits in the North American context, in this paper, I have shown that having dual citizenship is significantly positively linked to return visits compared to having only home country citizenship. In other words, dual citizenship is strongly linked to more mobility, allowing migrants to be simultaneously embedded in multiple contexts.…”
Section: Resultsmentioning
confidence: 62%
“…Conversely, transnational migration theory suggests that there may be a more positive association between integration in the host country and engagement in the homeland because they are separate yet compatible processes (Marcelli and Lowell, 2005;Levitt, 2008;Levitt and Lamba-Nieves, 2011). In line with the transnational perspective, several researchers have concluded early on that, in the North American context, migrants who are well integrated in the host country also cultivate relations with the home country (Itzigsohn and Saucedo, 2002;Guarnizo et al, 2003;Portes et al, 2003;Tamaki, 2011).…”
mentioning
confidence: 91%
“…Los expertos discutieron por mucho tiempo en el pasado si el involucramiento en procesos transnacionales representaba una alternativa a la integración, o era un proceso de asimilación de los migrantes en su nuevo país de asentamiento (Fitzgerald & Waldinger, 2004). Según Tamaki (2011), la asimilación y el transnacionalismo son paradigmas coexistentes.…”
Section: Transnacionalismounclassified
“…However, "analyses find little evidence of widespread, intensive transnationalism in the second generation" (Bachmeier et al 2013), as most of these adults are oriented overwhelmingly to their life in their country of birth (Kasinitz et al 2002;Rumbaut 2002;Haller and Landolt 2005;Tamaki 2011;Fokkema et al 2012). For example, among the Turks, Moroccans and former Yugoslavs in 15 European cities, 63.5% have no intention of ever taking up long-term residence in their parents' country of birth (Bachmeier et al 2013, 279).…”
Section: Emigration Of Children Of Immigrantsmentioning
confidence: 99%